UJI SIFAT KIMIA TANAH BERPIRIT AKIBAT LAMA PENGERINGAN DAN KEDALAMAN MUKA AIR TANAH - DEWI YULIANA E (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
ABSTRAK This research consisted of green house experiment prepared in completing randomize design in 3 replications. The treatment includes the combination of 2 factors (depth water table: 20, 40 cm below the pyrite layer; light of drying:2,4,6 and 8 weeks). The control is inundated soil. The longer the drying pyrit and the deeper water table, the soil pH, the content of ferro and soluble sulpfate decrease, on the other hand the ferri and Al-exchangeable increase.